How high-commitment HRM relates to PC violation and outcomes: The mediating role of supervisor support and PC fulfilment at individual and organizational levels. Issue 3 (June 2020) - Latorre, Felisa; Ramos, José; Gracia, Francisco J.; Tomás, Inés
Abstract: Psychological contract (PC) constitutes a theoretical framework for; explaining labor relationships, and it has been considered as a; mediation step between structural variables and processes and work and; organizational outcomes. Whereas PC (un)fulfillment; showed consistent relationships with variables such as job satisfaction, organizational commitment, performance, or absenteeism, the effects of PC; violation (emotional answers that develop after perceptions of PC; breach) have been less investigated. In addition, structural antecedents; of PC constructs had included Human Resources (HR) practices. This paper aims to extend; research on PC and its role as a mediator between HR practices and work; outcomes, both at individual and organizational levels. Specifically, we; examined the impact of human resource practices on employee performance; and sickness absences through a sequence of supervisor support, PC; fulfillment and PC violation. In a sample of 4648 employees from 214; companies of seven different countries, our results indicate that high-commitment; human resource practices were significantly and negatively; related to PC violation through supervisor support and positively to PC; fulfillment; in turn, PC violation was negatively related to employee; performance and positively to sick leave. These relationships at the; individual level were partially replicated at the organizational level, developing partial homologous models and showing that shared perceptions; about HR practices lead to shared perceptions on PC affecting collective; outcomes. Therefore, the findings shed new light on PC theory, regarding; the mediating role of PC constructs and negative emotions in the; relationships between HR practices and support from supervisors and performance at individual and organizational levels.